PRESSURE INJURY DEVELOPMENT AND CARE COMPLEXITY IN PATIENTS AT AN EMERGENCY SERVICE - Soares, Luzia Célia Batista; Silva, Drieli Oliveira; Cunha, Juliana Xavier Pinheiro da; Pires, Patrícia da Silva; Cardoso, Luiz Gustavo Vieira (Cogitare Enfermagem, 2022)
Objective: to assess pressure injury development and its association with care complexity in patients treated at an emergency service. Method: a prospective cohort and observational study conducted from August to October 2020 with patients treated in the emergency unit from a public hospital in southwest Bahia, Brazil. A specific form created for the study, the Braden Scale and the Perroca Classification Instrument were used for data collection. The data were analyzed by means of descriptive analysis and the Pearson’s chi-square test. Results: the sample consisted in 225 patients. The incidence of pressure injury was 9.3%. It mainly affected women (61.9%) in the intermediate (57.1%) and semi-intensive (42.9%) care levels. There was an association between care complexity and pressure injury development (p<0.001). Conclusion: the importance of evaluating care complexity in the patients treated at the emergency services is emphasized to provide safe care and reduce adverse events.